Germany's Rational Choice of Conventional Energy in the Context of Energy Security - Mergera Akbar Synergy Putra Agung (Universitas Medan Area, 2025)
This article aims to analyze the behavior of Germany, which is still heavily dependent on conventional energy despite its commitment to using renewable energy. The problem is focused on energy, which is one of the essential aspects of human life but is also dangerous for humanity's future. This is caused by exploiting conventional energy sources such as coal, hurting the ecosystem and the surrounding environment. Therefore, countries have taken the initiative to minimize the impact of this environmental damage by forming the Paris Agreement. One of the key points in this agreement is the reduction of the Earth's temperature and replacing conventional energy with renewable energy. As a country that ratified the Paris Agreement, Germany is committed to using renewable energy as its energy source. However, Germany has not been able to commit fully and still depends on conventional energy sources. This article will use Charles Glaser's theory of rational choice and a qualitative approach to analyze the issues raised. This article concludes that Germany's dependence on conventional energy sources is due to regional security factors and the relatively high price of renewable energy. The existence of this article is expected to make an essential contribution to the study of geopolitics, energy, and contemporary international relations.